Hands-on ensemble learning with Python : build highly optimized ensemble machine learning models using scikit-learn and Keras /: build highly optimized ensemble machine learning models using scikit-learn and Keras. (2019) - Kyriakides, George; Margaritis, Konstantinos G
No abstract available